2011
DOI: 10.1186/1471-2164-12-181
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor I revealed as family of promoter binding transcription activators

Abstract: BackgroundMultiplex experimental assays coupled to computational predictions are being increasingly employed for the simultaneous analysis of many specimens at the genome scale, which quickly generates very large amounts of data. However, inferring valuable biological information from the comparisons of very large genomic datasets still represents an enormous challenge.ResultsAs a study model, we chose the NFI/CTF family of mammalian transcription factors and we compared the results obtained from a genome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…All antibodies used had all been previously used for ChIP and validated for their specificity. Immunoprecipitations were with mouse anti-ASCL1 (BD Pharmingen) (Castro et al 2006), rabbit anti TCF3 (Santa Cruz, sc-349) (Lin et al 2010), rabbit anti-OLIG2 (Millipore, AB9610) (Mazzoni et al 2011), rabbit anti-MAX (Santa Cruz, sc-197) (Rahl et al 2010), goat anti-NFI (Santa Cruz, sc-30918) (Pjanic et al 2011;Martynoga et al 2013), goat anti-SOX2 (Santa Cruz sc-17320) (Chen et al 2008), rabbit anti-SOX9 (Millipore, AB5535) (Mead et al 2013), and goat anti-SOX21 (R&D systems, AF3538) (Matsuda et al 2012). Primers used for ChIP-PCR are listed in Supplemental Table S5.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%
“…All antibodies used had all been previously used for ChIP and validated for their specificity. Immunoprecipitations were with mouse anti-ASCL1 (BD Pharmingen) (Castro et al 2006), rabbit anti TCF3 (Santa Cruz, sc-349) (Lin et al 2010), rabbit anti-OLIG2 (Millipore, AB9610) (Mazzoni et al 2011), rabbit anti-MAX (Santa Cruz, sc-197) (Rahl et al 2010), goat anti-NFI (Santa Cruz, sc-30918) (Pjanic et al 2011;Martynoga et al 2013), goat anti-SOX2 (Santa Cruz sc-17320) (Chen et al 2008), rabbit anti-SOX9 (Millipore, AB5535) (Mead et al 2013), and goat anti-SOX21 (R&D systems, AF3538) (Matsuda et al 2012). Primers used for ChIP-PCR are listed in Supplemental Table S5.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%
“…The NF-I transcription factors bind to the dyad symmetric consensus sequence TTGGCNNNNNGCCAA and to individual half-sites with reduced affinity (Gronostajski et al, 1985;Meisterernst et al, 1988). Previous studies have found that NF-I transcription factors preferentially bind DNA target sites that are located close to transcription start sites and mainly act as activators of transcription of downstream target genes (Pjanic et al, 2011). In this study, we provide in vivo evidence that Hh signaling participates in root development using lineage tracing and cell ablation of Gli1 + cells.…”
Section: Introductionmentioning
confidence: 74%
“…5F,G). Previous studies have demonstrated that NF-I transcription factors preferentially bind their DNA target sites around transcription start sites and that they mainly act as activators of transcription (Pjanic et al, 2011). Therefore, we searched for NF-I binding sites within 2.5 kb upstream of the transcription start site of Hhip using two different web servers.…”
Section: Nfic Inhibits the Hh Signaling Pathway Via Hhipmentioning
confidence: 99%
See 1 more Smart Citation
“…S4A-C). To examine NFI protein binding to the NS cell genome, we performed a ChIP-seq analysis with an antibody that specifically recognizes the four NFI factors, which are closely related in sequence (Mason et al 2009;Pjanic et al 2011). NFI factors bound to 25,807 high-confidence sites in quiescent NS cells (Fig.…”
Section: Widespread Binding Of Nfi Tfs To Quiescent Ns Cell Enhancersmentioning
confidence: 99%